TEMPLE AS A CULTURAL MILESTONE OF CHINESE ETHNIC IN GORONTALO 1967-2000 - Tuke, Wahyudin; Mondong, Tonny Iskandar; Malae, Andris K. (CV. Fahr Publishing, 2025)
This study aims to examine the role of the temple as a center of culture and ethnic Chinese identity in Gorontalo in the period 1967 to 2000. In the socio-political context that suppressed ethnic cultural expression, especially during the New Order, the temple remained as a symbol of spiritual life as well as a fortress for preserving ancestral traditions. The method used in this study is a qualitative research method using a descriptive analysis approach where this study includes observation, interviews and documentation. The results of the analysis show that despite facing restrictions on cultural identity nationally, the temple in Gorontalo is able to become a space for adaptation and subtle cultural resistance. The temple is also a place of social interaction for various ethnic groups in Gorontalo. This finding shows the importance of the temple as a representation of cultural resilience and ethnic identity in Indonesia's multicultural society.